The extent of employing comprehensive quality standards in the preparation and training courses for Arabic language teachers and their teachers in the teaching methods for education directorates. - Mahdi, Ali Fadhil (Al-Adab Journal, 2020)
The current research aims to know (the extent to which comprehensive quality standards are used in the courses of preparing and training Arabic language teachers in teaching methods for education directorates). To achieve this goal , the researcher choses his research community represented by the six general directorates in Baghdad Governorate for the academic year (2018-2019), and the researcher has used the observation form that includes three areas of the comprehensive quality standards represented in (the first field the criteria for planning and preparing for the lesson, the second field is for implementing the lesson, and the third field is for evaluating the lesson. The list of the observation form included in its final form (42) paragraphs, and the researcher has relied on extracting honesty . These criteria has been offered to a group of experts and arbitrators in the Arabic language, methods of teaching and measurement and evaluation to show their opinion on their validity and express their opinions in them. The researcher has adopted the direct observation of the Likert scale because it is characterized by accuracy, comprehensiveness and consistency, and the researcher has used the statistical means appropriate for his research represented by Weighted mean, percentage weight, and Pearson correlation coefficient, and after the researcher has analyzed the results, it has appeared as follows: The second field includes the implementation of the lesson in the first place, while the first field is the criteria for preparation and implementation of the lesson has become second, while the third field of evaluation criteria remains the same in the third place, and in light of the research results the researcher concludes that the courses that have been held in the directorates of preparation and training included comprehensive quality standards for Arabic language teachers for the primary stage have not at the required level, and it lacked many standards that confirm modern programs in light of technological development and progress to keep pace with what is new and modern that serves the educational process in general. The researcher recommends several recommendations, the most prominent of which are: to familiarize themselves with the experiences of developed countries in the preparation and training programs that undertake to the development of the educational institution, especially Arabic language teachers, and urged the trainees to use modern methods, strategies, methods and programs that have an active role in contributing within the classroom. The researcher suggests conducting several studies, the most prominent of which are: conducting a similar study for secondary school teachers in total quality standards in later courses.